NILAI-NILAI PENDIDIKAN BUDI PEKERTI MASYARAKAT JAWA DALAM TRADISI MAGUTI - Kodrat Eko Putro Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Maguti is a tradition that still exists in the Ngawi community, East Java. This study aims to describe the meaning of equipment symbols and the process of implementation as well as the values of character education contained in the Maguti tradition. The method used in this research is qualitative method. This research was conducted in twenty places in Ngawi Regency, namely Jagir Village, Tulakan, Bayem Taman, Bayem Sidoarjo, Jagir Krajan, Kalitengah, Tempon, Kedungjambe, Plembeku, Gedangan, Mojoagung, Miripencil, Mirirejo, Tretes, Duwet, Duwet Plasong, Duwet Dawungan, Mojorejo, Jomblang, Sampung, Karangdempel. Equipment and process in the implementation of the Maguti tradition as the main study in this study. This research was conducted in Ngawi, East Java, Indonesia. The results of the study are that there are symbols in the form of equipment and the process of implementing the tradition of Maguti. Equipment in the tradition of Maguti are bucu, jenang abang putih, jenang sepuh, banyu suci, kembang setaman, sego udhuk, sego golong, gedhang setangkep, asahan, kopat lepet . Budi Pekerti’s educational values contained in the Maguti tradition are religious values, values of independence, values of caring, values of responsibility, values of mutual respect, values of honesty, and creative values.